2019
DOI: 10.4322/2526-8910.ctoar1926
|View full text |Cite
|
Sign up to set email alerts
|

Substance use to enhance occupational performance and experience: a critical interpretive synthesis

Abstract: Introduction: Substance use, as an occupation, is typically portrayed as problematic and the target of occupational therapy intervention and remediation. At the same time, psychoactive substances may be used to enhance mood, cognition, occupational performance, and/or experience, a perspective that is largely absent from occupation scholarship. Objective: We examine substance use in relation to the enhancement of occupation, drawing on the theoretical notion of agential realism. This theory suggests that in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 79 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…Despite this hegemonic approach to understanding substance use, it too is an occupation with multiple, nuanced, complex and even contradictory meanings. Psychoactive substances -whether legal or illegal, prescribed or widely available -may be used as part of spiritual ceremony and ritual (Boiteux et al, 2014;Labate, 2014) or to enhance mood, cognition, occupations (Kiepek et al, 2019b). Such substances may be used to alter the experience of other occupations, such as taking psychedelics to increase the pleasure of listening to music, or using cannabis to make housework more enjoyable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this hegemonic approach to understanding substance use, it too is an occupation with multiple, nuanced, complex and even contradictory meanings. Psychoactive substances -whether legal or illegal, prescribed or widely available -may be used as part of spiritual ceremony and ritual (Boiteux et al, 2014;Labate, 2014) or to enhance mood, cognition, occupations (Kiepek et al, 2019b). Such substances may be used to alter the experience of other occupations, such as taking psychedelics to increase the pleasure of listening to music, or using cannabis to make housework more enjoyable.…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere we propose alternative ways of conceptualizing 'meaning of occupation' (Kiepek et al, unpublished data) and 'substance use' (Kiepek et al, 2019b), but here we take up the challenge of the activity theory of concepts: to uncover values that inform dominant concepts. We have drawn on Engestrom's work on activity theory.…”
Section: Introductionmentioning
confidence: 99%
“…Kiepek et al 43 identified occupations as discursively “positive” and focused on how the relationship between occupational engagement and improved health and well-being can result in the implicit exclusion of activities considered “negative,” “unhealthy,” or “deviant,” with the potential to stigmatize and marginalize individuals or groups. “This has effectively silenced a significant realm of human experience, namely, occupations that are considered within dominant worldviews and societal groups to be unhealthy, illegal, and/or deviant.” 45 Some authors have argued that drug use 46 - 50 or addiction 46 , 51 , 52 is an occupation. Looking critically at the realm of healthcare, drug use and drug abuse have been deemed undesirable behaviors by society, 46 and typically labeled as problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Looking critically at the realm of healthcare, drug use and drug abuse have been deemed undesirable behaviors by society, 46 and typically labeled as problematic. 49 Thus, they are almost always viewed as an object of intervention and remediation in occupational therapy, with healthcare professionals eager to help clients abandon it. 46…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation